Workshop on Utilizing Artificial Intelligence (AI) for Teachers as a Learning Aid at Bina Insani Elementary IT School Semarang - Andik Prakasa Hadi; Rudjiono; Ahmad Zainudin; Setiyo Adi Nugroho; Agus Priyadi (Pusat Riset dan Inovasi Nasional, 2024)
The utilization of technology has influenced many aspects of life, and one of the fields affected is education. Basic education must adapt to the evolving era influenced by technology. The implementation of a workshop on the utilization of AI as a learning tool is based on observations and interviews with the headmaster of SD IT Bina Insani Semarang. This workshop introduces AI technology to the teachers of SD IT Bina Insani, along with its advantages and disadvantages. During the workshop, participants not only receive theoretical material but also engage in practical exercises in utilizing AI, guided by the team from PPM Universitas STEKOM Semarang. The evaluation of participants' understanding of the material on the use of AI is conducted directly during the practical sessions, considering the participants' active involvement throughout the workshop.